Germination And Growth Responses Of Greengram (Vigna Radiata (L.) R. Wilczek) And Blackgram (Vigna Mungo (L.) Hepper) Against Allelopathic Potential Of Vitex Negundo L. - KAVITHA.D; K.ARUMUGAM; PRABHAKARAN.J (International Journal of Pharma and Bio Sciences, 2012)
Allelopathy refers to the beneficial or harmful effects of one plant on another plant by the release of chemicals from plant parts by leaching, root exudation, volatilization, residue decomposition and other processes in both natural and agricultural systems. The present study has been made to evaluate the allelopathic potential of Vitex negundo L.against germination, growth and biochemical constituents changes of two pulses namely, green gram (Vigna radiata(L.) R.Wilczek) and blackgram (Vigna mungo (L.). Hepper). Various concentrations of (2.5, 5, 10, 15, 20 25%) aqueous leaf extracts were prepared from matured leaves of V. negundo and germination studies were conducted. The lower concentrations (2.5 and 5%) of leaf extracts stimulated the seed germination, growth and biochemical constituents (Chl., aminoacid, protein and total sugar) of black gram and green gram. In higher concentrations an inhibitory effect was observed in all the parameters studied in two pulses and the inhibitory effects were more prominent in green gram than black gram seedlings.